Remarks by Prof. Daniel Mugendi, Principal Embu University College on the occasion of the signing of the Memorandum Of Understanding (Mou) - Mugendi, Daniel N. (My University, 2014)
Remarks by Prof. Daniel Mugendi, Principal Embu University College on the occasion of the signing of the Memorandum Of Understanding (Mou) between Embu University College and Kenya Union of Post Primary Education Teachers (KUPPET) held on friday, october 3, 2014 at 9.30 am at Embu University College grounds
Keywords: Speech